2013
DOI: 10.1108/k-10-2012-0096
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of project members considering capability and personality balance

Abstract: Purpose -This paper aims to construct for the first time a link between the project members' assignment and personality balance. Design/methodology/approach -This study develops a project assignment quantitative model that maximizes the team's personality balance while meeting the capability requirements. Findings -The findings indicate that a more balanced project team that contributes to project performance can be obtained before project starts. Research limitations/implications -This paper is limited to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It helps senior management select the right candidate who will have the best performance in the project. Finally, the study by Wei, Lai, and Wei (2013) proposed a model that measures the level of imbalance in the project team which allows the project manager to carefully select the project team members to ensure the success of the project.…”
Section: Relationship Between Project-based Organization and Recruitmmentioning
confidence: 99%
“…It helps senior management select the right candidate who will have the best performance in the project. Finally, the study by Wei, Lai, and Wei (2013) proposed a model that measures the level of imbalance in the project team which allows the project manager to carefully select the project team members to ensure the success of the project.…”
Section: Relationship Between Project-based Organization and Recruitmmentioning
confidence: 99%
“…Examination of the literature on the project team formation indicated that many of the existing studies are concerned with the formation of teams based on the psychological and sociological competencies including personality, leadership, communication skills and decision-making abilities (Wei et al , 2013). Technical knowledge is the most widely used measure in the team formation literature for selecting team members (Chen and Lin, 2004; Fan et al , 2009; Otero et al , 2012; Wi et al , 2009; Zhang and Zhang, 2013).…”
Section: Introductionmentioning
confidence: 99%